Research of the deployment of the consulting engineer profession in Ukraine. Public requirements for the profession responsibilities. International practice of implementing standards - Tugay, O.; Troian, R. (Ways to Improve Construction Efficiency, 2024)
The article is based on the analysis of legal requirements and regulations of Ukraine as for the approval of qualification features of the consulting engineer profession [1]. Given the expertise of international institutions acquired through international forms of sub-contract agreements, which greatly impacts all participants of the investment in construction, the article highlights the objectives of a rapid development in Ukraine of the engineering and consulting service market model integrated in the generally recognized international industrial standards. The international practice and deployment of the new consulting engineer profession is assessed in compliance with the decision made under the Decree of the President of Ukraine “On Certain Measures to Create Condition for the Development and Improvement of Motorway Quality” [2]. The data brought to the article and the analysis of the research suggest using the international practice in construction of both regular structures and engineering works. The target indicator implies an opportunity to apply international standards that, in their turn, will contribute to a better adaptation of the best global practices in Ukraine, provided that there are coordination and cooperation established with international communities. The necessity to adjust the established standard form of agreement approved by the central executive authorities to the relevant international standards in effect as for unified interpretation and understanding of distinguishing features. The research unfolds a complete set of responsibilities required for the consulting engineer profession and streamlining of the profession structure in pursuance of categories in terms of their simplification, leading to a more comprehensive monitoring, high quality project management, and construction quality assurance. Decisions made on the basis of international forms of agreements accepted worldwide will promote a quick transfer to the unified system involving communication with international financial aid providers and organizations that, amidst the wartime and complicated economic position in Ukraine, have accumulated sufficient resource along with Ukraine’s government to ensure that immediate expenditures for national security and defence, critical infrastructure maintenance are made. This issue becomes increasingly focal within the meaning of the greater task through the development and recovery of the country after the aggression waged by the Russian Federation. Therefore, the essential interaction project provides for cooperation with international organizations, financial institutions and foundations as for sharing expertise and developments in attracting global knowledge and forms of investment and construction.